Tensor calculus and analytical dynamics : A classical introduction to holonomic and nonholonomic tensor calculus; and its principle applications to the Lagrangean dynamics of constrained mechanical systems /: A classical introduction to holonomic and nonholonomic tensor calculus; and its principle applications to the Lagrangean dynamics of constrained mechanical systems. ([2018?]) - Papastavridis, J. G (John G.)
No abstract available